Genome group classification and diversity analysis of talas and rutai banana, two local cultivars from East Kalimantan, based on morphological characters - Widi Sunaryo; Ahmad Mulyadi; NURHASANAH (Society for Indonesian Biodiversity, 2019)
Abstract. Sunaryo W, Mulyadi A, Nurhasanah. 2019. Genome group classification and diversity analysis of talas and rutai banana, two local cultivars from East Kalimantan, based on morphological characters. Biodiversitas 20: 2355-2367. Talas and rutai banana are two local cultivars grown in East Kalimantan and long-time used as dessert or cooking bananas for traditional food and cakes, but unfortunately, their taxonomic and genetic status are still little known. This study was conducted to explore their taxonomic and genetic status through morphological observation, genomic group classification and diversity analysis of talas and rutai banana compared to other recognized and identified bananas in Indonesia, i.e., liar/monyet, Ambon, tanduk and klutuk banana. In total 108 morphological characters were observed on site of growing area using the “Descriptors for Banana (Musa spp.)” morphological indicators. The genome group classification was carried out using Simmonds and Shepherd scoring system toward fifteen key banana characters. The diversity analysis was performed using Hierarchy Cluster Analysis at MINITAB 17.1 software based on the selected characters of the highest Principal Component Analysis (PCA) values. The morphological observation showed that the characters of talas and rutai banana are much closely related to those of belonging to M. acuminata although some characters showed balbisiana-type. In addition, liar/monyet and klutuk banana morphological characters were exactly matched with the M. acuminata and M. balbisiana accessions. Furthermore, most of Ambon banana morphological characters are similar to M. acuminata, but tanduk banana had a combination characters between M. acuminate and M. balbisiana. The genome group classification showed that talas and rutai banana are the AAB genotype, while liar/monyet, Ambon, tanduk, and klutuk were grouped into AA, AAA, AB, and BB genotype, respectively. The diversity analysis showed that talas and rutai banana have a very high similarity about 75% and closed related to AA/AAA genotype i.e., liar/monyet and Ambon with similarities level of 45%.